2021
DOI: 10.1017/bpp.2021.10
|View full text |Cite
|
Sign up to set email alerts
|

Do nudges crowd out prosocial behavior?

Abstract: Both theory on motivational crowding and recent empirical evidence suggest that nudging may sometimes backfire and actually crowd out prosocial behavior, due to decreased intrinsic motivation and warm glow. In this study, we tested this claim by investigating the effects of three types of nudges (default nudge, social norm nudge, and moral nudge) on donations to charity in a preregistered online experiment (N = 1098). Furthermore, we manipulated the transparency of the nudges across conditions by explicitly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
(44 reference statements)
0
5
0
1
Order By: Relevance
“…A handful experiments have studied other nudges than defaults. Gråd et al (2021) found no influence from disclosure of a social norm or a moral appeal nudge in an experiment on charitable giving. Zhuo et al (2023) studied a list order salience nudge (products displayed in order of carbon footprint) to encourage green consumption, with the same result.…”
Section: Empirical Findings About Transparency and Nudgingmentioning
confidence: 83%
See 1 more Smart Citation
“…A handful experiments have studied other nudges than defaults. Gråd et al (2021) found no influence from disclosure of a social norm or a moral appeal nudge in an experiment on charitable giving. Zhuo et al (2023) studied a list order salience nudge (products displayed in order of carbon footprint) to encourage green consumption, with the same result.…”
Section: Empirical Findings About Transparency and Nudgingmentioning
confidence: 83%
“…Among the empirical studies, the largest group of experiments concern default nudges applied in consequential (real stakes) choices. Here, the effects of message-induced transparency have been tested with charity donations (Bruns et al, 2018;Michaelsen et al, 2020Michaelsen et al, , 2021aGråd et al, 2021), agreement to extra low-paid/unpaid work in research studies (Steffel et al, 2016;Michaelsen et al, 2021b, experiment 1b;Paunov et al, 2019aPaunov et al, , 2019bPaunov et al, , 2020Wachner et al, 2020Wachner et al, , 2021van Rookhuijzen et al, 2023) and food choices (Steffel et al, 2016, experiment 1c; notably the only field experiment in this category). Gråd et al is the sole study reporting increased transparency to reduce the impact of the nudge, with a drop from 62% to 50% of participants partly donating a 50¢ bonus to charity.…”
Section: Empirical Findings About Transparency and Nudgingmentioning
confidence: 99%
“…These norms can be made salient, for instance, by including information about other people's CWA usage behavior in marketing campaigns. Such social norm nudges have already been shown to be effective in the context of prosocial behavior ( Gråd, Erlandsson, & Tinghög, 2021 ) or pro-environmental behavior (e.g., Farrow, Grolleau, & Ibanez, 2017 ; Kaiser, Arnold, & Otto, 2014 ). Such similarities are not surprising, since pro-environmental and prosocial behaviors most likely stem from the same individual propensity ( Otto, Pensini, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, people may react with a psychological reactance in situations where they feel that they are being manipulated into making certain choices ( Gråd et al, 2021 ). Although nudges, in theory, should preserve the freedom of choice, they can still amount to some level of pressure or result in a feeling that one should behave in a certain way.…”
Section: Methodsmentioning
confidence: 99%